Formulation of Avocado Juice with Coconut Water Potentially Lowers Hypertension - Sariningsih, Eka; Srimiati, Mia (Universitas Islam Negeri Walisongo Semarang, 2018)
Avocado is a fruit that high unsaturated fatty acid, while coconut water is fluid which has high potassium. The objective of this study was to assess the formulation of avocado juice with coconut water that could potentially reduce hypertension. The design of the study was an experimental with the degree of subsititution of coconut water as treatments. There were 3 kinds of treatment, i.e. F1 (75% avocado and 25% coconut water), F2 (50% avocado and 50% coconut water), F3 (25% avocado and 75% coconut water) and F0 (without coconut water but using water). Avocado juice product with 75% avocado substitution and 25% coconut water (F1) was a best formula determined by the hedonic test. This formula contained 68,48% (%w/w) water, 3,12% (%w/w) ash content, 4,45% (%w/w) fat content, 1,76% (%w/w) protein content, 21,07% (%w/w) carbohydrate content, 2163,8 (mg/kg) potassium content, 9,20% (%w/w) linoleic acid content, 1,11% (%w/w) linolenic acid content and 42,4% (%w/w) of total unsaturated fatty acid. This product could potentially reduce and prevent hypertension, because in one serving size (200cc) contain 432,76 mg of potassium (claim source of potassium).